Diseño de un plan de mejora del sistema de producción en una empresa de ebanistería a través del método Lean Manufacturing (2024)
This degree project has been worked in a cabinetmaking that makes wood-based products in Ovejas, Sucre. In this theoretical framework, the aim of this investigation is the Lean Manufacturing Appliances' application to improve the production. There was an assessment of the current cabinetmaking industry situation that was carried out through a self-diagnosis in every company's area about its demands and the first semester in 2024 performance. Diagrams, among other diagrams, such as Ishikawa, cause and effect, were used to identify potential problems in the organization; VSM, Value Stream Mapping, to understand the production process; FMEA, Failure Mode and Effects Analysis, to identify and evaluate process errors; and the Pareto diagram to classify the most defective products. Finally, a plan of action was proposed where the probable failures that the cabinetmaker's goes through were organized, and practicable solutions were established for each of them in order to improve the processes and continue improving continuously.